Control of the tennis stroke and metabolic responses through a new specific tennis field test - Caballero, P.; Dominguez, G.; de Teresa, C.; Feriche, B. (Archivos de medicina del deporte, 2008)
The endurance and success of stroke are some of the key point factors of tennis performance. There is a lack of specific field tennis tests to prescribe and control training performance; therefore it is necessary to investigate on new field test that allows relating the physiological parameters to the technical. Aim: The aim of this preliminary study was to apply a new specific tennis field test to know the relationship between the workload in metabolic zones and success or efficiency of stroke (ES) and determine a model of response. Methods: The study was realized by 5 tennis players (age 23 ± 1,9 years; height 174.9 ± 5.7 cm; weight 68.1 ± 5.7 kg; training per week 8.2 ± 2 hours). All subjects performed two incremental protocols to exhaustion: laboratory test (treadmill test) and a tennis specific field test. The field test consisted of repeated strokes (forehand and backhand) during 1 min, with 20 sec of rest. In both tests, heart rate (HR) and rating of perceived exertion (RPE) was monitored; the ventilatory thresholds were determined in the laboratory test. Results: The relationship between the metabolic zones by workload and ES was kept constant (> 60% ES) up to work near anaerobic threshold, where it started to decrease (> 10 % ES per workload). We have obtained three different types of response: a) Type 1: better ES in mixed zone, b) Type 2: better ES in aerobic zone, c) Type 3: ES stable in the 3 zones. Conclusion: The new specific tennis field test is a practical tool that allows an objective control of the training performance. The efficiency of stroke is better in aerobic zone (before VT1), maintain a regular response in mixed zone (between VT1-VT2) and decrease near anaerobic threshold (VT2). We find three types of response: Type 1 mixed, Type 2 aerobic and Type 3 stable